Investigating cardiovascular risk in premenopausal women on oral contraceptives: Systematic review with meta-analysis - Fabunmi, Oyesanmi A.; Dludla, Phiwayinkosi V.; Nkambule, Bongani B. (Frontiers in Cardiovascular Medicine, 2023)
Background The use of oral contraceptives (OCs) is associated with an increased risk of cardiovascular events such as arterial and venous thrombosis (VTE). Cardiovascular diseases (CVDs) are the leading cause of death worldwide, with low- and middle-income nations accounting for over three-quarter of CVD deaths. The aim of this systematic review is to provide a comprehensive synthesis of the available evidence on the link between OC use and CVD risk in premenopausal women and to further assess the role of geographic disparities in the reported prevalence of CVD risk in women on OCs. Methods A comprehensive search of databases such as MEDLINE, Academic Search Complete, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Health Source: Nursing/Academic Edition was conducted, right from the inception to the present, by using the EBSCOhost search engine. The Cochrane Central Register of Clinical trials (CENTRAL) was also searched to augment relevant sources of information. OpenGrey, which is a repository of information providing open access to bibliographical references, was searched and the reference list of the selected studies was also scanned. The potential risk of bias of the included studies was assessed using the modified Downs and Black checklist. Data analysis was performed using the Review Manager (RevMan) version 5.3. Results We included 25 studies that comprised 3,245 participants, of which 1,605 (49.5%) are OC users, while 1,640 (50.5%) are non-OC users. A total of 15 studies were included for meta-analysis, and the overall pooled estimates suggested a significant increase in the traditional cardiovascular risk variables [standardized mean difference (SMD) = 0.73, (0.46, 0.99) (Z = 5.41, p < 0.001)] and little to no difference in endothelial activation among OC users when compared with non-OC users [SMD = −0.11, (−0.81, 0.60) (Z = 0.30, p = 0.76)]. Europe [SMD = 0.03, (−0.21, 0.27), (Z = 0.25 p = 0.88)] had the least effect size, while North America had the highest effect size [SMD = 1.86, (−0.31, 4.04), (Z = 1.68 p = 0.09)] for CVD risk in OC users when compared with non-OC users. Conclusion The use of OCs suggests a significant increase in the prevalence of traditional cardiovascular risk variables with little to no difference in the risk of endothelial dysfunction when compared with non-OC users, and the magnitude of CVD risks varies across different geographical regions. Registration and protocol This systematic review was registered in the international prospective register of systematic reviews (PROSPERO) under the registration number: CRD42020216169.